Chronic Traumatic Encephalopathy and the Availability Cascade. Issue 3 (September 2014) - Solomon, Gary S.; Sills, Allen
Abstract : : Chronic traumatic encephalopathy (CTE) in sports has been known for > 85 years, and has experienced a resurgence of interest over the past decade, both in the media and in the scientific community. However, there appears to be a disconnection between the public's perception of CTE and the currently available scientific data. The cognitive bias known as the "availability cascade" has been suggested as a reason to explain this rift in knowledge. This review summarizes and updates the history of CTE in sports, discusses recent epidemiological and autopsy studies, summarizes the evidence base related to CTE in sports, and offers recommendations for future directions.